Optimal Initial Time Point of Local Radiotherapy for Unresectable Lung Adenocarcinoma: A Retrospective Analysis on Overall Arrangement of Local Radiotherapy in Advanced Lung Adenocarcinoma - Li, Xinge; Wang, Jie; Chang, Xu; Gao, Zhenhua; Teng, Feifei; Meng, Xue; Yu, Jinming (Frontiers in Oncology, 2022)
Local radiotherapy (LRT) is reported to be of survival benefit for advanced non-small cell lung cancer (NSCLC) in accumulating evidence, but researches on the optimal initial time point remains scarce. This IRB-approved retrospective analysis identified patients diagnosed with stage IIIb-IV unresectable lung adenocarcinoma who initiated front-line LRT at our institution between 2017 and 2020. The receiver operating characteristic (ROC) curve analyses were used to cut off the initial time of LRT (before and beyond 53 days). Patients were divided into two groups: one early to initiate radiotherapy group (≤53 days, EAR group), and one deferred radiotherapy group (>53 days, DEF group). Kaplan-Meier method was used to estimated time-to-event endpoints, Cox proportional hazards model was used to find out predictors of progression free survival (PFS) and overall survival (OS). A total of 265 patients with a median age of 57 were enrolled. The median follow-up time was 26.4 months (ranging from 2.2 to 69.7 months). The mOS was 38.6 months and mPFS was 12.7 months. age>60, bone and brain metastases, multi sites metastases and EGFR 19 mutation were independent predictors associated with OS. Early initiation of local radiotherapy within 53 days after diagnosis resulted in better PFS, but not in OS. A better OS was observed in patients with bone metastasis underwent local radiotherapy initiated within 53 days.